Investigation of rib optical waveguide using beam propagation method (BPM) - 288933 Mohamad Nazib Adon; Abu Bakar Mohammad, 1959-; Norazan Mohd. Kassim; Student Conference on Research and Development (2001 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2001)
40